Culprit Arteries in Patients with Inferior Wall Myocardial Infarction (IWMI) With St Segment Depression in Lead AVR: Culprit Arteries in Patients with Inferior Wall Myocardial Infarction - Raza, Asad; Ali, Fayaz; Bano, Nasreen; Yasmeen, .; Sumaiya, .; Ali, Muneeb; Fazal, Adnan; Fazal, Kamran (Pakistan Journal of Health Sciences, 2023)
ACS is an imbalance between the myocardial oxygen demand and consumption of oxygen by the heart. While coronary plaque rupture, which results in STEMI, is almost always the cause of this mismatch development of thrombus blocking a coronary artery. Objective: To determine the frequency of culprit arteries in patients with inferior wall myocardial infarction (IWMI) with ST Segment depression in Lead AVR. Methods: This cross sectional study was conducted at Department of Adult Cardiology, NICVD, Karachi, Pakistan from November 4, 2020 to May 3, 2021. All patients who fulfilled the inclusion criteria were enrolled and consent was taken. All patients were initially stabilized and then were prepared for coronary angiography. Interpretation of coronary angiogram was done to assess the culprit arteries i.e. LCX, RCA. Data were collected in proforma. Results. Out of 317 patients, 233 (73.5%) were male while 84 (26.5%) were female with mean age of 51.4±12.4 years. Left circumflex coronary artery was found in 184 (58%) patients. Right coronary artery was found in 133 (42%) patients. Conclusions: This study concludes that LCX artery is more likely to be culprit in patients with inferior wall myocardial infarction and ST-segment depression in lead AVR. STEMI patients with IWMI should be worked up for the presence of culprit arteries to ensure adequate treatment